2023
DOI: 10.1111/myc.13673
|View full text |Cite
|
Sign up to set email alerts
|

Onychoscopic characteristics of Trichophyton rubrum and Trichophyton interdigitalis fungal infections: A multicentric study

Michela Starace,
Elisa Milan,
Giovanni Summa
et al.

Abstract: BackgroundTrichophyton rubrum and Trichophyton mentagrophytes variant interdigitalis are the most frequent etiologic agents of onychomycosis. Diagnosis of certainty requires mycological examination, which often results unfeasible.ObjectivesThe aim of our study is to describe pathogen specific dermoscopic features, allowing a differential diagnosis without the need for cultural examination, in order to prescribe the most appropriate treatment anyway.Patients and methodsWe conducted an observational retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This study's observation that only 59.91% of toenail OM cases exhibited nail spikes emphasizes the importance of not excluding OM solely based on the absence of this feature. Starace et al 5 . reported significant associations between spikes and Trichophyton rubrum infection and striae and infection from Trichophyton interdigitalis .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study's observation that only 59.91% of toenail OM cases exhibited nail spikes emphasizes the importance of not excluding OM solely based on the absence of this feature. Starace et al 5 . reported significant associations between spikes and Trichophyton rubrum infection and striae and infection from Trichophyton interdigitalis .…”
Section: Discussionmentioning
confidence: 99%
“…16,17 This study's observation that only 59.91% of toenail OM cases exhibited nail spikes emphasizes the importance of not excluding OM solely based on the absence of this feature. Starace et al 5 reported significant associations between spikes and Trichophyton rubrum infection and striae and infection from Trichophyton interdigitalis. We cannot analyze the correlation between the dermoscopic features and the pathogen type because only a few isolates for Trichophyton interdigitalis were captured in this study.…”
Section: Comparison Of Dermoscopic Features In Psoriatic and Non-psor...mentioning
confidence: 99%
See 2 more Smart Citations